The Solomon Islands Early Childhood Development : SABER and NSA-ECD Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2016)
This report presents an analysis of the Early Childhood Development (ECD) subsector, including programs and policies that affect young children in the Solomon Islands. This was a collaborative effort between UNICEF and World Bank Group, as it combines World Bank Group’s SABER-ECD framework, which includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in the Solomon Islands, along with regional and international comparisons, as well as the regionally developed UNICEF National Situational Analysis-ECD, which takes a greater in-depth look at the following system components, which have been highlighted by the Pacific Region as priority components for quality Early Childhood Care and Education (ECCE) implementation: policy/legislation and governance; human resources; curriculum, child assessment, and environment; performance monitoring and assessment; and community partnerships. The government of the Solomon Islands (SIG) recognizes the importance of providing early learning opportunities for young children. In 2008 the Ministry of Education and Human Resources Development (MEHRD) endorsed a National Early Childhood Education Policy Statement, targeting age’s three to five, which states its commitment to develop a quality Early Childhood Education (ECE) sector. This commitment has been reflected in both the National Education Action Plan, 2013–2015, and the Education Strategic Framework, 2007–2015. However, the statement clearly identified ‘in relation to quality practice, the payment and training of teachers, relevant curriculum, effective management, community awareness about the value of ECCE and children’s access and participation in ECCE’ as challenges to the implementation of ECCE services.